Repairing paradise the restoration of nature in America's national parks - Lowry, William R. (William Robert), 1953- (Brookings Institution Press, 2009)
"Examines whether the U.S. can restore the most-loved crown jewels of its national park system, focusing on four ambitious efforts to reverse environmental damage. Combines field research with public policy analysis to portray the mission to restore the natural health and glory to some of the world's most wondrous places"--Provided by publisher.